2020
DOI: 10.21203/rs.3.rs-28635/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternal and perinatal outcomes and pharmacological management of Covid-19 infection in pregnancy: a systematic review protocol

Abstract: BackgroundOver 4.2 million confirmed cases and more than 285,000 deaths, COVID-19 pandemic continues to harm significant number of people worldwide. Several studies have reported the impact of COVID-19 in general population, however, there is scarcity of information related to pharmacological management, maternal and perinatal outcomes during the pandemic. Altered physiological, anatomical and immunological response during pregnancy makes it more susceptible to infections. Furthermore, during pregnancy, a woma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Questionnaire questions about whether mothers who are confirmed to have COVID-19 can breastfeed their babies, 27 respondents answered incorrectly, mothers who were confirmed to have COVID-19 were allowed to touch and hold their babies, and 32 respondents answered incorrectly. Mothers who breastfeed confirmed COVID-19 in the Parazzini study (2020) in 10 cases breastfeeding was allowed, with women wearing surgical masks and 2 women having a new diagnosis of COVID-19 infection in the postpartum period and being breastfed without a surgical mask, the two newborns tested positive for Covid-19 on the 1 st and 3 rd days [21]. This is similar to the Indonesian Ministry of Health (2020) breastfeeding during the COVID-19 pandemic, and it is not transmitted through breast milk because the transmission of this virus comes from droplets, so mothers must avoid using eating utensils at the same time as the fetus [22].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Questionnaire questions about whether mothers who are confirmed to have COVID-19 can breastfeed their babies, 27 respondents answered incorrectly, mothers who were confirmed to have COVID-19 were allowed to touch and hold their babies, and 32 respondents answered incorrectly. Mothers who breastfeed confirmed COVID-19 in the Parazzini study (2020) in 10 cases breastfeeding was allowed, with women wearing surgical masks and 2 women having a new diagnosis of COVID-19 infection in the postpartum period and being breastfed without a surgical mask, the two newborns tested positive for Covid-19 on the 1 st and 3 rd days [21]. This is similar to the Indonesian Ministry of Health (2020) breastfeeding during the COVID-19 pandemic, and it is not transmitted through breast milk because the transmission of this virus comes from droplets, so mothers must avoid using eating utensils at the same time as the fetus [22].…”
Section: Discussionmentioning
confidence: 98%
“…The rate of premature birth in pregnant women with COVID-19 is higher than pregnant women without the disease [24]. Parazzini (2020) said elective cesarean section was performed in 18 cases, in 8 cases the indications were not related to Covid-19 infection, but in 10 cases the indications were worsening shortness of breath or other Covid-19-related symptoms in women who tried vaginal delivery [21].…”
Section: Discussionmentioning
confidence: 99%
“…Várias opções de tratamento incluem, fármacos antivirais e combinações, antimaláricos, anti-histamínicos, esteroides e antipiréticos. Enquanto as estratégias de tratamento para COVID-19 diferem entre os países, a OMS e os Centros de Controle de Doenças (CDC) e as diretrizes de prevenção são muito gerais, e ambos aconselham o manejo de pacientes grávidas e pediátricas com cuidado (THOMAS et al, 2020). Nesse sentido, o uso de agentes terapêuticos deve ser feito após uma análise individual de risco-benefício e uma cuidadosa consideração dos potenciais benefícios para a mãe e segurança fetal (TRAPANI JÚNIOR et al, 2020).…”
Section: A Prática Regular De Exercício Físico Com Enfoque Aos Sinais Sintomas E Problemas Geraisunclassified
“…24,36,37 Some case reports and small studies observed increased complications and adverse maternal and fetal outcome with COVID-19 severe disease. [46][47][48] Royal College of Obstetricians and Gynecologists Guideline has reported some adverse outcome with COVID-19 in pregnancy in the form of slight increased risk of preterm delivery, premature rupture of membranes, maternal sepsis, preeclampsia, and postpartum hemorrhage. 12 In their systematic review and meta-analysis on COVID-19 in pregnancy, Capobianco et al 49 observed increased maternal and neonatal complications.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%